An Experimental Study on Effect of Palm – Shell Waste Additive to Cement Strenght Enhancement - Adi Novriansyah; Novrianti Novrianti; Mursyidah U; Sepria Catur Hadiguna (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Enhancing the cement strength through attaching chemical additive has been popular to meet the required condition for a particular well-cementing job. However, due to a low oil-price phenomenon, pouring and additive should be reconsidered because it can raise the cost and make the project become uneconomic. Another additive material in nanocomposite form will be introduced through this experimental study. The nanocomposite material consist of silica nanoparticle, known as “Nanosilica” and a palm-shell-waste, which is abundant in Indonesia. Before making a nanocomposite, the palm-shell should be burned to obtain a charcoal form, ground and sieved to attain a uniform size. The study focuses on the two parameters, compressive strength and shear bond strength, which can reflect the strength of the cement. These values are obtained by performing a biaxial loading test to the cement sample. Various samples with different concentration of nanocomposite should be prepared and following the mixing, drying, and hardening process before the loading test is carried out. The result from the test shows a positive indication for compressive strength and shear bond strength values, according to the representative well cementing standards. Increasing the nanocomposite concentration on the cement will increase these values. Furthermore, an investigation on the temperature effect confirms that the sample with 700oC burning temperature have highest compressive-strength and shear-bond-strength values. This is a potential opportunity utilizing a waste-based material to produce another product with higher economic value.